Transcript-specific loss-of-function variants in VPS16 are enriched in patients with dystonia - Park, Joohyun; Reilaender, Annemarie; Petry-Schmelzer, Jan N.; Stöbe, Petra; Cordts, Isabell; Harmuth, Florian; Rautenberg, Maren; Woerz, Sarah E.; Demidov, German; Sturm, Marc; Ossowski, Stephan; Schwaibold, Eva; et al. (Neurology. Genetics, 2022)
Background and Objectives Our objective was to improve rare variant interpretation using statistical measures as well as publicly accessible annotation of expression levels and tissue specificity of different splice isoforms. We describe rare VPS16 variants observed in patients with dystonia and patients without dystonia, elaborate on our interpretation of VPS16 variants affecting different transcripts, and provide detailed clinical description of the movement disorder caused by VPS16 variants. - Methods In-house exome and genome data sets (n = 11,539) were screened for rare heterozygous missense and putative loss-of-function (pLoF) variants in VPS16. Using pext (proportion expressed across transcripts) values from the Genome Aggregation Database (gnomAD), we differentiated variants affecting weakly and highly expressed exons/transcripts and applied statistical measures to systematically identify disease-associated genetic variation among patients with dystonia (n = 280). - Results Six different heterozygous pLoFs in VPS16 transcripts were identified in 13 individuals. Three of these pLoFs occurred in 9 individuals with different phenotypes, and 3 pLoFs were identified in 4 unrelated individuals with early-onset dystonia. Although pLoFs were enriched in the dystonia cohort (n = 280; p = 2.04 × 10−4; 4/280 cases vs 9/11,259 controls; Fisher exact test), it was not exome-wide significant. According to the pext values in gnomAD, all 3 pLoFs observed in the patients with dystonia were located in the highly expressed canonical transcript ENST00000380445.3, whereas 2 of 3 pLoFs detected in 8 individuals without dystonia were located in the first exon of the noncanonical transcript ENST00000380443.3 that is weakly expressed across all tissues. Taking these biological implications into account, pLoFs involving the canonical transcript were exome-wide significantly enriched in patients with dystonia (p = 1.67 × 10−6; 4/280 cases vs 1/11,259 controls; Fisher exact test). All VPS16 patients showed mild progressive dystonia with writer's cramp as the presenting symptom between age 7 and 34 years (mean 20 years) that often progressed to generalized dystonia and was even accompanied by hyperkinetic movements and myoclonus in 1 patient. - Discussion Our data provide strong evidence for VPS16 pLoFs to be implicated in dystonia and knowledge on exon resolution expression levels as well as statistical measures proved to be useful for variant interpretation.
First published December 7, 2021
Gesehen am 22.03.2022